Do All Intellectual Capital Dimension Affects Innovation Capability? (Evidence from Indonesian Food and Beverage Industry) - Dian Mayastika Molthar; Nurul Indarti (KINERJA, 2021)
Using a survey in 120 companies in the food and beverage industry such restaurants and café, manufacture, and retail in Indonesia, this study discusses the effect of intellectual capital on innovation capability. The results prove that not all of intellectual capital dimension support innovation capability. Structural capital and relational capital are knowledge assets that play an important role for the company's ability to innovate. In addition, other findings from this study reveal that human capital has no significant effect on innovation capability. That is because in the context of three companies in the food and beverage industry in Indonesia, the innovation decision is not related to the employee or human capital aspects. Furthermore, this research also has not been able to prove that relational capital moderates the positive influence of human capital on innovation capability. That is because the formation of human capital aspects such skills of employees in this industry are not related to the relations and collaboration of the company.Keywords: human capital, structural capital, relational capital, innovation capability